2016
DOI: 10.1080/21645515.2016.1157241
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and infant outcomes among women vaccinated against pertussis during pregnancy

Abstract: Tetanus, diphtheria, and acellular pertussis (Tdap) vaccination is recommended for all women during each pregnancy to prevent pertussis in young infants. However, data on the safety of this protective measure are limited and conflicting. To assess maternal and infant outcomes associated with administration of this vaccine during pregnancy, we reviewed medical records of 1,759 women who delivered a singleton infant at a southeast Texas public hospital between November 1, 2012 and June 30, 2014. After excluding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 25 publications
(25 reference statements)
7
53
1
Order By: Relevance
“…Equally reassuring are the findings of other well-designed observational studies,50 51 64–66 including a US retrospective observational cohort study using data from two California Vaccine Safety datalinks,64 a more recent analysis from seven US Vaccine Safety Datalinks in the year following ACIP recommendations for antenatal Tdap vaccination,50 a retrospective review of medical records of 1759 women who delivered a singleton infant in Texas during 2012–201465 and a prospective follow-up study of 403 infants in New Zealand whose mothers had received Tdap antenatally following a pertussis epidemic in 2012 67…”
Section: Resultsmentioning
confidence: 98%
“…Equally reassuring are the findings of other well-designed observational studies,50 51 64–66 including a US retrospective observational cohort study using data from two California Vaccine Safety datalinks,64 a more recent analysis from seven US Vaccine Safety Datalinks in the year following ACIP recommendations for antenatal Tdap vaccination,50 a retrospective review of medical records of 1759 women who delivered a singleton infant in Texas during 2012–201465 and a prospective follow-up study of 403 infants in New Zealand whose mothers had received Tdap antenatally following a pertussis epidemic in 2012 67…”
Section: Resultsmentioning
confidence: 98%
“…The current study both confirmed an earlier-reported chorioamnionitis association and reported a new association with post-partum hemorrhage. An earlier British study did not demonstrate an association between postpartum hemorrhage and prenatal Tdap,[35] and among three prior studies assessing chorioamnionitis and prenatal Tdap,[18, 36, 37] only one demonstrated an association; the largest examined 123,494 pregnancies in regional electronic health records, of which 21% received prenatal Tdap, and found RR=1.19 (95% CI: 1.13–1.26) for chorioamnionitis among women who received prenatal Tdap, with chorioamnionitis diagnosed in 6.1% of immunized women and 5.5% in unimmunized women, higher than our national, claims-based IPTW-weighted risks of 3.3% in optimally-immunized women and 3.0% of unimmunized women. [18] Our primary analysis found an association similar in magnitude, however, these findings should be interpreted with caution; in sensitivity analyses of women who also received prenatal influenza immunization and were therefore more similar in terms of healthcare access and behaviors, we did not observe an association between Tdap and chorioamnionitis, and the post-partum hemorrhage association was attenuated to RR=1.05 (95% CI: 0.99–1.10); this suggests the potential for residual confounding by behavioral or clinical factors uncaptured by claims.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies evaluated birth defects after influenza vaccines and have found no safety concerns (Pasternak et al, 2012;Chambers et al, 2013;Polyzos et al, 2015;McMillan et al, 2015). A smaller number of studies have assessed Tdap vaccines given to pregnant women and no associations with birth defects have been noted (Shakib et al, 2013;Berenson et al, 2016;Regan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%